Memahami Risiko dan Penghargaan Dalam Investasi : Peran Perilaku Keuangan - Adnyaswari, Ni Putu; Sinarwati, Ni Kadek (Sains: Jurnal Manajemen dan Bisnis, 2023)
This research aims to in-depth understanding of risk and reward in the investment context and the role played by individual financial behavior in the investment decision-making process. This research uses a qualitative approach with a literature study to explore the understanding of risks and rewards in investment, especially the role of financial behavior in the investment decision making process. Risk and reward are the two main aspects that influence investment decisions, and an individual's financial behavior plays an important role in how they assess, manage and respond to these factors. The results of this study provide a deeper understanding of how individuals' financial behavior influences their investment decision making and influences the performance of their portfolios. In addition, this research provides a foundation for further research in the field of behavioral finance and investment, with the aim of developing smarter and more informed strategies in dealing with the complexity of the financial world.